Effects of Gallid Herpesvirus 2 Marek’s Disease Challenge Virus and Attenuated Vaccine Virus CVI988/Rispens on Immune Adhesion of Erythrocytes of Chickens - Tian , W.X.; Sun, N.; Ning, G.B.; Zhang, D.J.; Feng, J.; Lv, T.X.; Wang, Y.; Wang, H.M.; Wang, X.H.; Li, F. (International Journal of Poultry Science, 2013)
This study was designed to investigate the influence of Gallid herpesvirus 2 Marek’s Disease challenge virus and different inoculated routes of attenuated vaccine virus CVI988/Rispens on immune adhesion of erythrocytes in chickens. One day old chicks were randomly divided into a control group (C), an experimental group challenged with Jing-1 challenge strain (V), a second and third experimental group individually injected intra-abdominally (IA) or subcutaneously (SC) with vaccine strain, CVI988/Rispens. The erythrocyte immune adhesion was evaluated with yeast rosette-forming tests of red blood cell complement receptor type 1 (RBC-CR1) and red blood cell immune complex (RBC-IC). It was found that chickens from group V had fewer erythrocytes. During this time, the rate of RBC-IC rosette formation was higher in group V except on days 3 and 20. While the rate of RBC-CR1 rosette formation was lower in group V except on the 26th day when the number of RBC-CR1 rosettes was extremely higher. The rate of RBC-CR1 rosette formation and RBCs count was higher in group IA than that of SC. The results suggest that challenge virus lead to immune suppression, a decline in the immune adhesion of RBCs followed by a rebound during the later stages of infection; effects on RBC immunity were increased after inoculate attenuated vaccines strains; IA vaccination route may enhance the immune adhesion of RBCs comparing with SC route; and an improvement in the RBC immunity adhesion during the later stages of infection may have resulted from a compensatory immune response to immune organ atrophy and the decrease of RBCs.